2004
DOI: 10.1086/381754
|View full text |Cite
|
Sign up to set email alerts
|

Use of a T Cell–Based Assay for Monitoring Efficacy of Antituberculosis Therapy

Abstract: Monitoring the efficacy of antituberculosis therapy is crucial both for the individual patient and for better control of the spread of tuberculosis. We studied 18 patients with microbiologically confirmed tuberculosis, both at the time of diagnosis and 3 months after they started therapy, using an in vitro assay that detects T cell-mediated interferon- gamma response to selected peptides of Mycobacterium tuberculosis-specific early secretory antigenic target 6 (ESAT-6) protein. All patients had positive result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
159
4
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 13 publications
12
159
4
4
Order By: Relevance
“…The decreasing kinetics observed for the IGRA response upon treatment of M. kansasii disease were similar to those reported for TB or latent TB, although this pattern was not observed in all studies (Bocchino et al, 2010;Carrara et al, 2004;Chiappini et al, 2012;Katiyar et al, 2008;Kobashi et al, 2009a;Mori, 2009;Pai et al, 2006). Several hypotheses were raised for these discrepancies, such as reinfection in high burden settings, persistence of effector T-cells and within-subject variability (Chiappini et al, 2012;Ewer et al, 2006;Pai et al, 2006;van Zyl-Smit et al, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…The decreasing kinetics observed for the IGRA response upon treatment of M. kansasii disease were similar to those reported for TB or latent TB, although this pattern was not observed in all studies (Bocchino et al, 2010;Carrara et al, 2004;Chiappini et al, 2012;Katiyar et al, 2008;Kobashi et al, 2009a;Mori, 2009;Pai et al, 2006). Several hypotheses were raised for these discrepancies, such as reinfection in high burden settings, persistence of effector T-cells and within-subject variability (Chiappini et al, 2012;Ewer et al, 2006;Pai et al, 2006;van Zyl-Smit et al, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Individuals with a strong IFN-c response to the ESAT-6 compared to those with low IFN-c response had a tenfold increased risk of subsequently developing clinical TB in the 1-2-year period after the exposure [11]. This observation was consistent with the fact that successful antituberculosis therapy was found to decrease the level of IFN-c in response to specific M.tb antigens, ESAT-6 and CFP-10 [31][32][33]. Adetifa et al [34] reported a rising qualitative and quantitative ELISPOT counts of IFN-c producing T lymphocytes in response to ESAT-6/CFP-10 peptides in a close TB contact in Gambia, who developed active disease over a 5-month period.…”
Section: Discussionsupporting
confidence: 62%
“…ATB patients presented a positivity in the typical range of 70-85%, established with IFNγ-based assays [ 11 ]; recent contacts are reported to have about 50% probability of MTB infection (43% established in our RC group), and the positivity of 38% in HW does not differ from the OSHA annual occupational TB risk for 50 bed-wards with more than 100 admissions for TB per year, equivalent to 34.5% [15]. Indeed, the response to the RD1 antigens was shown to be lower in MTB-infected subjects without active disease than in ATB patients, and decreased under effective chemotherapy treatment together with the bacterial load [ 16,17 ].…”
mentioning
confidence: 61%